2021
DOI: 10.1186/s12245-021-00383-4
|View full text |Cite
|
Sign up to set email alerts
|

The use of a formative OSCE to prepare emergency medicine residents for summative OSCEs: a mixed-methods cohort study

Abstract: Background The objective structured clinical examination (OSCE) is a part of emergency medicine (EM) examinations such as the Masters of Medicine in Emergency Medicine (MMed) examination and the equivalent Member of the Royal College of Emergency Medicine (MRCEM) examination. The use of formative OSCEs to prepare EM residents for summative OSCEs has not been investigated. This study aimed to evaluate the role of formative OSCEs in preparing EM residents for the MMed and MRCEM OSCE. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Showing a progression between the two OSCE sessions in naïve students demonstrated the impact of training in real conditions. These results are frequently found in studies evaluating the skills of students or doctors in the context of medical simulation [ 18 , 24 , 25 ]. OSCE scores were found to have high reliability and demonstrated significant differences in performance by year of training, providing evidence for the validity of OSCE scores as markers of progress in learners at different levels of training [ 26 ].…”
Section: Discussionmentioning
confidence: 59%
“…Showing a progression between the two OSCE sessions in naïve students demonstrated the impact of training in real conditions. These results are frequently found in studies evaluating the skills of students or doctors in the context of medical simulation [ 18 , 24 , 25 ]. OSCE scores were found to have high reliability and demonstrated significant differences in performance by year of training, providing evidence for the validity of OSCE scores as markers of progress in learners at different levels of training [ 26 ].…”
Section: Discussionmentioning
confidence: 59%
“…(20) Lee et al discovered similar results in a mixed cohort study of emergency medicine residents. (21) In a 2019 study conducted in the United States, Sampat et al discovered that students who completed a practice exam performed much higher in their end-of-clinic OSCE. (22) Another study conducted in 2017 at the Caribbean Medical School found a significant improvement in academic performance following the use of formative assessment in students in the basic science years.…”
Section: Discussionmentioning
confidence: 99%
“…Since Dr. Ronald Harden’s inception of the objective structured clinical examination (OSCE) in the 1970’s the OSCE has spread around the globe and cemented itself as an educational pillar spanning all levels of training and a wide range of health professions [ 1 6 ]. Today, OSCE’s serve both summative and formative functions [ 7 9 ]. They offer the ability to have nearly identical encounters which increased the possibility of reliable, valid and replicable assessments with definable goals for performance which allows for the use of OSCEs as a summative assessment of a trainee.…”
Section: Introductionmentioning
confidence: 99%